ON THE DIFFERENTIAL DIAGNOSIS LYMPHADENOPATHY IN CHILDREN - E. S. Kharlamova; V. F. Uchaykin; N. Yu. Egorova; V. O. Trunov; Ya. P. Sulavko (LLC "Diagnostics and Vaccines", 2015)
The article shows an example of differential diagnosis of cervical lymphadenopathy in a child of 7 years old with mixed bacterial bartonello-clamydophilic infection on the background of persistent viral Epstein-Barr virus and human herpesvirus infection type 6.